Płyta Reissnera o Niejednorodności Wykładniczej - Gawęcki, A. (Engineering Transactions, 1973)
The paper presents the displacement equations for a linear-clastic, isotropic Reissner plate of constant thickness, the Young modulus of the material being an exponential function of the middle surface coordinates. The equations are reduced to three separate equations for the displacement functions. In the case of an infinite plate, the singular solutions corresponding to concentrated forces and couples are given. The numerical example demonstrates the method of solution of certain boundary value problems for partially bounded plates. The considerations are generally referred to a simplified model of a Reissner plate in which the transversal normal stresses are disregarded. This simplification was made in view of the results of the paper by R. GANOWICZ [3].